Analisis Yuridis terhadap Peran Bagian Samapta dalam Penanganan Peristiwa Unjuk Rasa Berdasarkan Undang-Undang Nomor 9 Tahun 1998 Tentang Kemerdekaan Menyampaikan Pendapat di Muka Umum - Habinsaran Parhusip; Muhammad Ridwan Lubis (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
The freedom of expression in public is a human right guaranteed in Indonesia's legal system through Law No. 9 of 1998. The handling of public demonstrations by the Indonesian National Police, particularly the Samapta unit, plays a strategic role in maintaining order and security during protests. This study aims to analyze the role of the Samapta unit in managing public demonstrations, identify the challenges faced, and examine the implementation of human rights principles in crowd control. Using a normative legal method with a juridical normative approach, this study analyzes secondary data in the form of regulations, legal literature, and official documents, as well as primary data from Law No. 9 of 1998, Law No. 2 of 2002 concerning the Indonesian National Police, and related regulations. The results show that the role of the Samapta unit in managing public demonstrations includes three main aspects: preventive, repressive, and educational. The preventive role is carried out through coordination and security preparations as stipulated in Article 10 of Law No. 9 of 1998, the repressive role involves the dispersal of protests under certain conditions as per Article 15, and the educational role is implemented through socialization and community guidance. However, the implementation of human rights in protest security still faces challenges in aspects such as proportionality of force, non-discrimination, accountability, and public participation. The study concludes that, although it has a strong legal foundation, improvements in regulations, human resources capacity, and supervision systems are needed in handling public demonstrations.